PENGEMBANGAN E-MODULE BERORIENTASI PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI OPERASI HITUNG PECAHAN SISWA KELAS V SD - Ardiyanto, Eka Yudha (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2025)
The aim of this research is to analyze the development procedures, validity and effectiveness of e-module oriented on PBL to improve critical thinking skills in fifth grade elementary school students' fraction counting operation material. The type of research method carried out is development research or Research and Development (R & D) with the development procedure namely ADDIE, and data collection techniques in the form of teacher and student observation sheets, questionnaires for validation of material, media and learning experts, teacher and student response questionnaires, and knowledge tests. The e-module oriented on PBL was tested on 22 students of SDN Reksosari 01 and 6 students of SDN Reksosari 02 (experiment), and 13 students of SDN Reksosari 03 (control). Data analysis techniques include needs analysis, normality test, homogeneity test, and analysis of the effectiveness of e-module oriented on PBL products. The results of this research are: (1) the procedure for developing a e-module oriented on PBL using the ADDIE stages, (2) The results of the assessment by material, media and learning experts state that the e-module oriented on PBL is in the Good or Suitable for use category with an average percentage of 77, 7%, (3) e-module oriented on PBL is effective for improving critical thinking skills of fifth grade elementary school students. It can be seen from the average value of students' critical thinking skills between the pretest and posttest as well as the experimental group and the control group as targeted, namely that there is a significant difference (0.000 < 0.05).